Cooling performance of vaccine refrigeration box made of open-cell microporous polyurethane vacuum insulation panels - Haie Huo; Mengyi Ma; Fabing Wang; Yufeng Tan; Ziding Wang; Jianjun Zhang; Xiaobo Di (Case Studies in Thermal Engineering)
A vaccine refrigeration box made of open-cell microporous polyurethane (OCMPU) vacuum insulation panels (VIPs) is developed in this paper. Firstly, it is found that the vacuum degree in the OCMPU VIPs can be improved by drying the membrane material and core material and selecting the combined getter, the corresponding service life of which is approximately 5.9 years. Secondly, it is found that precooling has little effect on the thermal insulation effect, and the temperature change of the box corner is found to be obvious during transportation. The phase change material (PCM) located at the top of the box plays an important role in the thermal insulation performance of the refrigeration box. However, blindly increasing the thickness of VIPs does not significantly improve the thermal insulation performance of vaccine refrigeration boxes. Finally, the performance of the refrigeration box made of OCMPU VIPs is compared with other mainstream refrigeration boxes through experiments. It is found that the thermal insulation time of the OCMPU VIPs refrigeration box is nearly 3 times that of the conventional polyurethane (PU) refrigeration boxes, and is 88 % of that of the fumed silica (FS) VIPs refrigeration box. However, refrigeration boxes made of OCMPU VIPs have the advantage of lighter weights than FS VIP refrigeration boxes.